Photomodulated Morphologies in Halogen Bond–Driven Assembly during Gel–Sol Transition. Issue 3 (22nd October 2018) - Hu, Haisi; Qiu, Yuan; Wang, Jing; Zhao, Dongxu; Wang, Hong; Wang, Qin; Liao, Yonggui; Peng, Haiyan; Xie, Xiaolin
Abstract: Photoresponsive supramolecular gels with various applications are being constantly pursued; however, achieving well‐defined morphology changes of gels via light irradiation remains a formidable challenge. In this study, a gel is prepared through halogen bond between azopyridine‐containing Azopy‐C10 and 1, 4‐tetrafluorodiiodobenzene. The gel exhibits gel–sol transition due to trans–cis isomerization of the azopyridine moiety upon UV irradiation. During this transition, the morphologies vary from flake to fluffy bobble‐like and finally to peony‐like with increasing exposure time, which is difficult to achieve in traditional assembly systems. The microstructure change is attributed to the variations of cis‐isomer content and halogen‐bonding strength. The supramolecular gel provides a novel method to achieve photomodulated morphologies and broadens the applications of such kind of materials, ranging from information storage to high‐tech anticounterfeit. Abstract : Herein, halogen bond acts as an important driving force to fabricate a supramolecular gels between azopyridine‐containing Azopy‐C10 and 1, 4‐diiodotetrafluorobenzene . During the gel–sol transition upon UV irradiation, the morphological changes from flake to fluffy bobble‐like and finally to peony‐like can be achieved, which are difficult to achieve by traditional assembly systems.